Determination of essential oil content in needles of selected species from the Pinaceae family - Korić, Emina; Nikšić, Haris; Gušić, Irma; Durić, Kemal (Archives of Pharmacy, 2022)
In order to determinate essential oil content, five species from the Pinaceae family were investigated. Plant material was collected in two locations in Bosnia and Herzegovina - Crepoljsko (Ozren Mountain) and Ruište (at the bottom of Mountain Prenj), in the spring period of 2020. Isolation and determination of the essential oil content was performed by Clevenger distillation, with a duration of 2.5 h. The results of determining the content of essential oils are expressed as the mean value of three consecutive distillations, for each species of the Pinaceae family. As a raw material for distillation process, the fresh, whole needles (leaves) of the tested species were used, as follows: Pinus sylvestris L. - collected in Crepolje; Pinus nigra J.F.Arnold - collected in Crepolje; Pinus heldreichi Christ - collected at Ruisht; Picea abies (L.) H.Karst. - collected at Ruište; Picea pungens Engelm. - collected in Crepolje. Qualitative analysis of the tested samples of essential oils was performed by thin layer chromatography (TLC). The presence of α-thujone, a mixture of α- and β-thujone , α-phelandrene, β-pinene, bornyl acetate and eucalyptol in the tested samples was examined. The determined content of essential oils ranging from 0.3 mL/100 g, in Pinus heldreichii needles, to 1.03 mL/100 g, in Picea abies needles. The applied chromatographic conditions enable adequate separation and identification of target molecules of interest in the tested samples.